2011
DOI: 10.3788/col201109.071406
|View full text |Cite
|
Sign up to set email alerts
|

稳定高效的半导体泵浦Yb:KGW飞秒激光器

Abstract: An efficient high-power diode-pumped femtosecond Yb:KGW laser is repored. Through optimization of energy density by semiconductor saturable absorber mirror, output power achieved 2.4 W with pulse duration of 350 fs and repetition rate of 53 MHz at a pump power of 12.5 W, corresponding to an optical-to-optical efficiency of 19.2%. We believe that it is the highest optical-to-optical efficiency for single-diode-pumped bulk Yb:KGW femtosecond lasers to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…For too-small mode size on the SESAM would lead to very fast oversaturation and limit the output power, while too-large mode size on the SESAM would hard to achieve stable mode-locking. [19] Therefore, the spot size is 390 µm on the surface of SESAM. The oscillator pulses were initially optimized in continuous wave (CW) operation.…”
Section: Resultsmentioning
confidence: 99%
“…For too-small mode size on the SESAM would lead to very fast oversaturation and limit the output power, while too-large mode size on the SESAM would hard to achieve stable mode-locking. [19] Therefore, the spot size is 390 µm on the surface of SESAM. The oscillator pulses were initially optimized in continuous wave (CW) operation.…”
Section: Resultsmentioning
confidence: 99%
“…So far, many Yb-doped gain media, such as Yb∶CaF 2 , Yb∶Y 3 Al 5 O 12 (Yb:YAG), Yb∶Ca 4 Gd,YOBO 3 3 (Yb:GdYCOB), Yb∶KYWO 4 2 (Yb:KYW), Yb∶KGWO 4 2 (Yb:KGW), Yb: CaGdAlO 4 (Yb:CALGO), and Yb∶CaYAlO 4 (Yb:CALYO), have proved to be suitable for mode-locked lasers and exhibited good laser performance [4][5][6][7][8][9][10] . Among these crystals, the Yb:KGW, Yb:CALGO, and Yb:CALYO crystals have the most potential as gain media, which are suitable for generating high-power lasers with short pulse duration [11][12][13][14][15] . Using a Yb:CALGO crystal, 96 fs pulses were obtained with average power of 12.5 W, which is the highest output power from sub-100-fs Yb-doped oscillators [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Then, 100 fs pulses have been demonstrated with 126 mW of output power based on the Yb:KGW crystal [24] . Furthermore, the Yb:KGW oscillator generated 350 fs pulses with 2.4 W of output power [14] . In 2008, Calendron of high-Q laser production Gmbh et al demonstrated 24 W CW laser using the dual Yb:KYW crystals and two LDs.…”
Section: Introductionmentioning
confidence: 99%
“…Yb-doped KGd(WO 4 ) 2 laser material is well suited to build diode-pumped pulse lasers in watts region [1] because of its large optical absorption, large emission cross section, [2] broad gain bandwidths of 24 nm, and good thermal conductivity of 3.3 W/m•K. These desirable properties have proved that the Yb:KGW laser is good for a number of applications, [3][4][5][6] and quite a few Yb:KGW lasers have been reported. [7][8][9] Pulsed lasers have been obtained by a semiconductor saturable absorber mirror, [10,11] carbon nanotubes, [12] graphene, [13,14] a combination of graphene and nanotube, [15] etc.…”
Section: Introductionmentioning
confidence: 99%